Regulation of reaction forces during the golf swing - McNitt-Gray, J. L.; Munaretto, J.; Zaferiou, A.; Requejo, P. S.; Flashner, H. (Sports Biomechanics, 2013)
During the golf swing, the reaction forces applied at the feet control translation and rotation of the body-club system. In this study, we hypothesized that skilled players using a 6-iron would regulate shot distance by scaling the magnitude of the resultant horizontal reaction force applied to the each foot with minimal modifications in force direction. Skilled players (n = 12) hit golf balls using a 6-iron. Shot distance was varied by hitting the ball as they would normally and when reducing shot distance using the same club. During each swing, reaction forces were measured using dual force plates (1200 Hz) and three-dimensional kinematics were simultaneously captured (110 Hz). The results indicate that, on average, the peak resultant horizontal reaction forces of the target leg were significantly less than normal (5%, p < 0.05) when reducing shot distance. No significant differences in the orientation of the peak resultant horizontal reaction forces were observed. Resultant horizontal reaction force-angle relationships within leg and temporal relationships between target and rear legs during the swing were consistent within player across shot conditions. Regulation of force magnitude with minimal modification in force direction is expected to provide advantages from muscle activation, coordination, and performance points of view.